Factors associated with school nurses' HPV vaccine attitudes for school-aged youth. Issue 5 (28th May 2017) - Rosen, Brittany L.; DiClemente, Ralph; Shepard, Allie L.; Wilson, Kelly L.; Fehr, Sara K.
Abstract: School nurses are at the intersection of the healthcare and school communities, thus, they can be considered opinion leaders in providing health advice – including information about the human papillomavirus (HPV) vaccine – to parents and students. This study examined school nurses' attitudes toward the HPV vaccine based on age, years as a school nurse, geographic location, urban vs. rural work setting, HPV and vaccine knowledge, perception of role as opinion leaders, and school district support in providing health education. Participants ( n = 413) were systematically sampled from the National Association of School Nurses' membership and completed a web-based survey. Multiple regression was used to predict positive HPV vaccine attitudes. The model was statistically significant accounting for 50.8% of the variance ( F [9, 400] = 45.96, p < .001). Positive attitudes regarding the HPV vaccine were predicted by higher HPV and vaccine knowledge ( β = .096, p < .001) and stronger perceptions of role as opinion leaders for the vaccine ( β = .665, p < .001). No other variables were found to be statistically significant. These results suggest knowledge is essential in predicting positive attitudes, but not the strongest predictor as perceptions of role as opinion leaders was more crucial in terms of predicting school nurses' positive attitudes towards HPV vaccine. Despite school nurses being seen as champions for adolescent vaccines, they need additional professional development to increase their HPV vaccine knowledge and attitudes to encourage parents and adolescents to consider the uptake of HPV vaccination. To engage school nurses' in promoting HPV vaccine uptake, interventions need to focus on increasing school nurses' perception of their role as opinion leaders for HPV vaccine and knowledge to increase positive attitudes towards HPV vaccination for youth.